PENINGKATAN MOTIVASI BELAJAR IPA MELALUI METODE PEMBELAJARAN QUANTUM TEACHING BAGI SISWA KELAS IV - Rohmanurmeta, Fauzatul Ma’rufah (Premiere Educandum, 2015)
At the elementary school level, sains learning still monotonous and uninteresting because elementary school system with classroom teachers to make the teachers have difficulty in using the right strategy. Teachers are required to achieve the target material that is quite a lot and should be comleted in each semester.This situation resulted in the lack of attention of student in the process of learning activities so that a low student motivation. Under these conditions, the purpose of this research is to improve students motivation through quantum teaching method of learning process in the fourth grade students of SDN 02 Wates Distric jenangan, Ponorogo.This research is a classroom action research (PTK), which consists of the first cycle and the second cycle. The study subjects were students of class 4 SDN 02 Wates wich consist 11 students. Collecting data in this study using a questionnaire to determine students motivation, and the observation sheet in the form of check list to determine the activity of students. Before held research student motivation is low. Then after research showed that motivation of students of cycle 1 45,5% and cycle II 82% increased 36,5%. Interpretation of student learning to learning in sycle 1 is 36% and cycle II increased to 82%. Student activity in I cycle was 27,3% and in the II cycle increased to 81,8%. The result showed that the use of quantum teaching methods can improve students motivation in learning sains SDN 02 wates.Keywords: motivation in learning, sains, quantum teaching methods